Integrated Pest Management in Plant Protection - Félix, Maria do Rosário (2018)
This manual has a main goal to give some basic achievements to the technicians and farmers about the means of control of the pests in their crops. The concept of Integrated Pest Management (IPM) emerged from the need of crops treatment with a low impact on natural ecosystems, reducing the chemicals applied and therefore the costs, treating only when necessary. This treatment integrates a combination of cultural, physical/mechanical, biological, and microbial/chemical pesticide control methods, to keep environmental impacts to a minimum.